Socioeconomic and Demographic Inequalities in Off-Label Prescription of Glucagon-Like Peptide-1 Receptor Agonists: A Swedish Descriptive Cohort Study - Laura Pazzagli; Ylva Trolle Lagerros (Obesity Facts)
Introduction: In Sweden, glucagon-like peptide-1 (GLP-1) receptor agonists are subsidized for diabetes indication but not for obesity. Unregulated off-label prescription of GLP-1 receptor agonists for obesity treatment may raise concerns about potential inequalities for both patient groups. This study aimed to describe socioeconomic and demographic characteristics of on- and off-label users of GLP-1 receptor agonists in persons without a diagnosis of diabetes. Methods: This is a Swedish descriptive register-based cohort study of persons who filled a prescription of a GLP-1 receptor agonist at least once during 2018–2022. Individuals were excluded from the study population if they had a diagnosis of diabetes or previous prescription fills of insulin/analogs at any time prior to the first filled prescription of a GLP-1 receptor agonist. Socioeconomic and demographic characteristics were described overall and stratified by sex and prior use of anti-obesity medications. Off-label use was defined by filled prescriptions of GLP-1 receptor agonists which are indicated for diabetes treatment. Results: The study population included 16,436 individuals, of which 70.1% were women, 30.7% had previously filled a prescription of anti-obesity medications, and 65.3% had Sweden as country of origin and 17.2% an Asian country. In the analyses stratified by sex, women were more likely to have an education longer than 9 years (84.8% vs. 78.3% in men). Nonetheless, women had lower annual individual (2,891.3 vs. 4,004.9 in men) and family disposable income (5,645.5 vs. 6,092.5 in men). Overall, on-label prescription was higher in women (49.2% vs. 30.9% in men), while off-label was more common among men (69% vs. 51% in women). Trends of GLP-1 users per 1,000 inhabitants showed four-fold variation between counties. Conclusion: High family disposable income and male sex are common among off-label GLP-1 receptor agonist users compared to users of the only on-label GLP-1 receptor agonist available in Sweden during the study period. Large variation between counties indicates different clinical practices and guideline interpretations.